Phytochemical Screening of Sorghum (Sorghum Sp) with Thin Layer Chromatography Method - Endang Noerhartati; Muhammad Farid Rizal; Elika Joeniarti (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
Sorghum is a food plant rich in benefits and has the advantage of being free gluten; it contains antioxidants and has a low glycemic index. The purpose of this research is to determine the content of compounds in sorghum. In the research, the variety of KD 4 sorghum has been used, which was macerated by absolute methanol. Results screening using thin-layer chromatography showed that methanol extract of sorghum contained flavonoid, phenol, triterpenoid, tannin, and saponin compounds, and finally, these compounds will be useful for pharmaceutical products.